2012
DOI: 10.1287/mnsc.1120.1519
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Valuation of Modularly Upgradeable Products

Abstract: A lthough product modularity is often advocated as a design strategy in the operations management literature, little is known about how consumers respond to modular products. In this research we undertake several experiments to explore consumer response to modularly upgradeable products in settings featuring technological change. We consider both the initial product choice (between a modularly upgradeable product and an integral one) and the subsequent upgrade decision (replacement of a module versus full prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 44 publications
0
29
0
4
Order By: Relevance
“…, Ülkü et al. ) and can be brought up‐to‐date without significant cost. But, it is unclear how this will affect for instance the frequency of product introduction.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
“…, Ülkü et al. ) and can be brought up‐to‐date without significant cost. But, it is unclear how this will affect for instance the frequency of product introduction.…”
Section: Discussion and Directions For Future Researchmentioning
confidence: 99%
“…The sample was recruited through Amazon.com's Mechanical Turk (MTurk) online subject pool where "requesters" (in our case, researchers) recruit "workers" (in our case, research participants) for the completion of "human intelligence tasks" (in our case, surveys) in exchange for wages. MTurk has become an accepted and popular recruitment tool among social scientists (e.g., Polman & Russo, 2012;Senecal, Wang, Thompson, & Kable, 2012;Skarlicki & Turner, 2014;Ulku, Dimofte, & Schmidt, 2012;West, Meserve, & Stanovich, 2012), and research suggests that scale reliability and in general psychometric properties are as good or better when scales are administered on MTurk as when they are administered via traditional methods (e.g., Behrend, Sharek, Meade, & Wiebe, 2011;Buhrmester, Kwang, & Gosling, 2011;Paolacci, Chandler, & Ipeirotis, 2010). In addition, a recent study examining the demographics of MTurk workers in the United States (Huff, 2014) demonstrated that the distribution of workers across industry is very similar to that of the distribution of the general U.S. population.…”
Section: Study 1: Item Generationmentioning
confidence: 99%
“…Other study revealed significant results regarding the acceptance of upgradeable products by customers [23]. Product update viability must be analyzed in greater depth by researchers and managers.…”
Section: Modularity In Usementioning
confidence: 92%
“…A process module, in turn, [3,4] Modularity Approaches related to the partitioning of the modularization strategy [5,21] Modular architecture The structure in which the functional components of the product are arranged into physical parts and how interactions occur among the parts through interfaces [18,22,23] Module A functional unit with standardized interfaces that can be combined to compose products [17,23] Interfaces Connections that allow interconnection, adjustment, and communication of the modules [3,24] Source: prepared by the authors based on published studies includes standardized and indivisible activities of the process [21]. Modularity in services can be defined as a way of using resources in a flexible manner.…”
Section: Modularity In Servicesmentioning
confidence: 99%